Implementation of Proxy at XYZ Inc. Study: Experiment on Network Performance Optimization - Fandi Ali Mustika; Muhammad Rifqi; Yuwan Jumaryadi; Febryo Ponco Sulistyo; Indah Ramadhani; Eko Prasetyo Pratomo (LPPM Universitas Islam 45 Bekasi, 2025)
The rapid development of information technology demands companies to have a network infrastructure that is not only fast but also secure and efficient. PT. XYZ, as a company engaged in distribution and customer service, faces challenges in managing increasing data traffic while maintaining the stability and security of its internal network. One strategic solution to address this issue is the implementation of a proxy server. A proxy server functions as an intermediary between users and the internet, enabling it to filter data requests, store cache, and restrict access to unwanted content. Thus, the implementation of a proxy server can improve bandwidth efficiency, accelerate access to frequently used websites, and strengthen network security systems through traffic monitoring and restriction. This research aims to implement and evaluate the effectiveness of using a proxy server within PT. XYZ’s environment. The evaluation results show that the use of a proxy server can enhance network efficiency and provide better protection against cyber threats. With a more controlled and secure system, the company can run its operations more optimally and sustainably.